Oligoclonal Bands in Cerebrospinal Fluid of Black Patients with Multiple Sclerosis. (29th July 2015) - Gama, Paulo Diniz da; Machado, Luís dos Ramos; Livramento, José Antonio; Gomes, Hélio Rodrigues; Adoni, Tarso; Morales, Rogério de Rizo; Gama, Rodrigo Assad Diniz da; Gama, Daniel Assad Diniz da; Lana-Peixoto, Marco Aurélio; Fragoso, Yara Dadalti; Callegaro, Dagoberto
Abstract : Genetic susceptibility is a well-recognized factor in the onset of multiple sclerosis (MS). The objective of this study was to determine the frequency of oligoclonal bands (OCB) restricted to the cerebrospinal fluid, in an ethnically mixed group of MS patients in the city of São Paulo, Brazil. Techniques used to detect OCB consisted of isoelectric focusing followed by immunoblotting. OCB were found in 49 (54.4%) out of 90 patients with clinically definite MS; out of the 23 brown/black patients, 17 (73.9%) were OCB+; out of the 66 white patients, 32 (48.5%) were OCB+; and the only patient yellow was OCB+ (p = 0.05 ). Analysis of the IgG index was also consistent with the findings, but with lower statistical significance. The data presented in our study show that the ethnic differences in MS extend to the immune response.